Research on employee performance management in MNCs. A call for expanding the psychological perspective: a research note. (4th March 2011) - Dewettinck, Koen; Remue, Jonathan
Based on a thorough review of the academic literature on global employee performance management and influenced by our own research on Employee Performance Management (EPM), we argue that this field of research has much to gain by expanding the psychological perspective. More specifically, we make three suggestions about how to deepen our understanding of how EPM can take shape in a multinational context. First, we propose that much can be gained by broadening our scope to both formal and informal elements of EPM. Second, we suggest that cross-cultural research on organisational behaviour provides very useful insights that have important implications for our domain. Finally, we argue that there is an accrued need for more research that starts from an employee perspective and we provide some theoretical frameworks we believe could be fruitfully applied and further tested within this intriguing field of interest.